Unusually Large Submandibular Sialoliths: Report of Two Cases - Alkurt, Meryem Toraman; Peker, Ilkay (European Journal of Dentistry, 2009)
Sialoliths are the most common diseases of the salivary glands. They may occur in any of the salivary gland ducts but are most common in Wharton’s duct and the submandibular gland. This report presents clinical and radiographical signs of two unusually large sialoliths. There were painless swellings on the floor of the mouth in both cases. Radiographical examination revealed large irregular radioopaque mass superimposed right canine and premolar areas. After the lesions were removed, histopathological examination was performed and lesions were diagnosed as sialoliths. (Eur J Dent 2009;3:135-139)
Keywords: Sialolith; Submandibular gland; Wharton’s duct